FUNGSI PARTAI DALAM PENDIDIKAN POLITIK MASYARAKAT DI KABUPATEN PINRANG - Zaldy, Satyva Camelia Putri; Maidin, Muhammad Sabir (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2020)
This article discusses about the review of Islamic State structure law to the political parties' function on giving political education for the society in Pinrang District using analysis of law number 2 of 2008 political parties. The main issues in this journal include the implementation of political education for the society by political parties, the participation of society in the Election in Pinrang District, and Siyasah views in giving the political education to the society by political parties in Pinrang District.The research type used in this journal is qualitative field research, using interviews, observations, and documentation. In the implementation of political education in society, political parties have performed their roles according to the statutory regulations. The level of society in the participation in the 2019 general elections is 86.80% with 230.958 votes of a total in 266.081 people registered in the permanent vote list.The implication of this research is the political parties should enrich society’s knowledge by creating work programs that is oriented towards political education in society.